The Application of KillerRed for Acute Protein Inactivation in Living Cells. Issue 1 (1st July 2014) - Jarvela, Timothy S.; Linstedt, Adam D.
Abstract: Generating loss of protein function is a powerful investigatory tool particularly if carried out on a physiologically relevant timescale in a live‐cell fluorescent imaging experiment. KillerRed mediated chromophore assisted light inactivation (CALI) uses genetic encoding for specificity and light for acute inactivation that can also be spatially restricted. This unit provides protocols for setting up and carrying out properly controlled KillerRed experiments during live‐cell imaging of cultured cells. Curr. Protoc. Cytom . 69:12.35.1‐12.35.10. © 2014 by John Wiley & Sons, Inc.